B-cell response in solid organ transplantation - Yi, Stephanie G.; Gaber, Ahmed Osama; Chen, Wenhao (Frontiers in Immunology, 2022)
The transcriptional regulation of B cell response to antigen stimulation is complex and involves an intricate network of dynamic signals from cytokines and transcription factors propagated from T cell interaction. Long-term alloimmunity, in the setting of organ transplantation, is dependent on this B cell response, which does not appear to be halted by current immunosuppressive regimens which are targeted at T cells. There is emerging evidence that B cells have a diverse response to solid organ transplantation that extends beyond plasma cell antibody production. In this review, we discuss the mechanistic pathways of B cell activation and differentiation as they relate to the transcriptional regulation of germinal center B cells, plasma cells and memory B cells in the setting of solid organ transplantation.